Variational transition-state theory study of the atmospheric reaction OH + O3 → HO2+ O 2 - Ju, Li-Ping (2007)
We report variational transition-state theory calculations for the OH + O3rarr HO2 + O2 reaction based on the recently reported double many-body expansion potential energy surface for ground-state HO4 [Chem Phys Lett 2000, 331, 474]. The barrier height of 1.884 kcal mol-1 is comparable to the value of 1.77-2.0 kcal mol-1 suggested by experimental measurements, both much smaller than the value of 2.16-5.11 kcal mol-1 predicted by previous ab initio calculations. The calculated rate constant shows good agreement with available experimental results and a previous theoretical dynamics prediction, thus implying that the previous ab initio calculations will significantly underestimate the rate constant. Variational and tunneling effects are found to be negligible over the temperature range 100-2000 K. The O1-O2 bond is shown to be spectator like during the reactive process, which confirms a previous theoretical dynamics prediction. © 2007 Wiley Periodicals, Inc. 39: 148-153, 2007